ANALISIS PERATAAN LABA PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN - Febi Fatimah; R. Deni Muhammad Danial; Faizal Mulia Z (Jurnal Ekonomi dan Bisnis, 2019)
The purpose of this study was to analyze the practice of income smoothing in food and beverageindustry companies. Income smoothing is the intentional reduction of earnings fluctuations inan effort to stabilize profits to be considered normal for a company. This data is obtained fromwww.idx.co.id. The population in this study were food and beverage companies listed on theIndonesia Stock Exchange for the period of 2014-2016. The sampling technique used wasusing the purposive sampling method from 16 samples to 10 samples used. The data analysistechnique of this research is descriptive statistical analysis techniques. To calculate incomesmoothing using the Eckel Index formula. The results of this study indicate that 6 companiescarry out income smoothing practices and 4 companies do not.Keywords: Income Smoothing, Index Eckel